Food Safety, from Farm to Fork Emerging and Re-Emerging Issues. - Kiio, Juliana (Cambridge Scholars Publisher, 2020)
Globally, there are many safety concerns emanating from the consumption of food, and are categorized as physical, biological and chemical hazards. This volume explores a number of safety issues pertaining to foods consumed across the globe today. It represents a useful resource for researchers, food handlers and legislative bodies as it presents key findings in the area of food safety, and details the findings of a number of scientific research studies conducted through surveys, laboratory analysis and environmental assessments. The findings indicate the presence of eminent food safety threats.